The Performance Comparation in Indonesia: Conventional Mutual Funds vs Sharia Mutual Funds - Apriadi Herlambang (Profesional Muda Cendekia Publishing, 2020)
This study aims to see, whether or not there is a reference to the performance of conventional and Islamic mutual funds in Indonesia with the Sharpe Index, Treynor Index and Jensen Index. The population of this research is Conventional Equity Mutual Funds and Sharia Equity Mutual Funds which are listed on the Indonesia Stock Exchange. Sampling was carried out using proposive judgment sampling method, namely the selected sample was invincible with predetermined selection criteria. The sample chosen is the monthly NAB of Islamic and conventional equity funds that were effective before January 1, 2016 and actively working until December 31, 2018, this is intended to obtain the latest information on the performance of equity mutual funds. Based on the sample selection criteria, it is obtained 20 mutual funds for conventional category stocks and 13 mutual funds for Islamic stocks that are active and publish their monthly NAB during the study period. This hypothesis testing is done in a comparative way, namely data analysis is done by using the Independent Sample T-Test. This analysis is carried out by comparing the returns, risks, and performance of conventional and Islamic mutual funds. Based on the results of the Independent Sample Test, it shows that there is a significant difference between the performance of Islamic equity funds and conventional equity funds using the Sharpe Index, Treynor Index and the Jensen Index